Program of the 19th annual research day: scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2018)
Our 19th Annual Research Day showcases the work of more than 150 aspiring scientists in Colorado State University's College of Veterinary Medicine and Biomedical Sciences. The day gives our rising stars vital experience presenting their research findings to a scientific audience through poster displays and talks. The day also provides young researchers with an avenue for feedback to help them develop ideas that, in many cases, will become lifelong scientific pursuits. In a sign of significance, the research projects on display are sponsored by two dozen well-respected companies, foundations, and institutions concerned with improving human, animal, and environmental well-being.

Includes the Zoetis Research Excellence Award winner, program of oral sessions and poster presentations.
19th annual CVMBS research day program
Colorado State University, College of Veterinary Medicine and Biomedical Sciences, 19th annual CVMBS research day scientific proceedings, program
Held on January 20, 2018 in the Lory Student Center, colorado State University.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses